Bowtie shaped substrate integrated waveguide bandpass filter - Baharudin, Z. (Springer Verlag, 2015)
A planar bandpass filter based on a technique that utilizes substrate integrated waveguide (SIW) is presented. The SIW based bandpass filter is implemented using a bowtie shaped resonator structure. The bowtie shaped filter exhibits similar performance as found in rectangular and circular shaped SIW based bandpass filters. This concept reduces the circuit foot print of SIW, along with miniaturization high quality factor is maintained by the structure. The design for single-pole resonator structure is presented; and by coupling the resonators a two-pole bowtie shaped SIW bandpass filter is achieved for the frequency of 7 GHz. The simulation result reveals that the filterâs insertion loss is better than 1 dB and return loss is less than 30 dB. Â© Springer International Publishing Switzerland 2015.